Блоґосфера як історичне джерело: до постановки проблеми - Михайлова, О.Ю. (Український історичний журнал, 2014)
Розвиток сучасної української історії неможливо уявити без леґалізації нового
типу історичних джерел – інформації, яка міститься в інтернет-повідомленнях.
На особливу увагу заслуговує блоґосфера – як її контент, так і статистичні дані.
Нижче подано короткий огляд методології роботи з матеріалами блоґосфери, зазначаються особливості й небезпеки використання цього нового типу джерел. The article provides a brief trial of a new type of historical sources, such as the
data contained in the messages of the Internet. The development of Ukrainian
contemporary history is unimaginable without the legalization of such historical
sources. The blogosphere, with its content and statistics, is particularly worthy
of researchers attention. The article includes an overview of the methodological
techniques and points to characteristics and dangers in usage of blogosphere as
new type of historical sources.